Outcomes of routine ilioinguinal lymph node dissection for palpable inguinal melanoma nodal metastasis. Issue 7 (22nd April 2014) - Glover, A. R.; Allan, C. P.; Wilkinson, M. J.; Strauss, D. C.; Thomas, J. M.; Hayes, A. J.
<x xml:space="preserve">Abstract</x> Background Patients who present with palpable inguinal melanoma nodal metastasis have two surgical options: inguinal or ilioinguinal lymph node dissection. Indications for either operation remain controversial. This study examined survival and recurrence outcomes following ilioinguinal dissection for patients with palpable inguinal nodal metastasis, and assessed the incidence and preoperative predictors of pelvic nodal metastasis. Methods This was a retrospective clinicopathological analysis of consecutive surgical patients with stage III malignant melanoma. All patients underwent a standardized ilioinguinal dissection at a specialist tertiary oncology hospital over a 12‐year period (1998–2010). Results Some 38·9 per cent of 113 patients had metastatic pelvic nodes. Over a median follow‐up of 31 months, the 5‐year overall survival rate was 28 per cent for patients with metastatic inguinal and pelvic nodes, and 51 per cent for those with inguinal nodal metastasis only (P = 0·002). The nodal basin control rate was 88·5 per cent. Despite no evidence of pelvic node involvement on preoperative computed tomography (CT), six patients (5·3 per cent) with a single metastatic inguinal lymph node had metastatic pelvic lymph nodes. Logistic regression analysis showed that the number of metastatic inguinal nodes (odds ratio 1·56; P = 0·021) and suspicious CT findings (odds ratio 9·89; P = 0·001) were both significantly associated with metastatic pelvic nodes. The specificity of CT was good (89·2 per cent) in detecting metastatic pelvic nodes, but the sensitivity was limited (57·9 per cent). Conclusion Metastatic pelvic nodes are common when palpable metastatic inguinal nodes are present. Long‐term survival can be achieved following their resection by ilioinguinal dissection. As metastatic pelvic nodes cannot be diagnosed reliably by preoperative CT, patients presenting with palpable inguinal nodal metastasis should be considered for ilioinguinal dissection.